Glutathione S-transferase gene family analysis and enzymatic properties of three selenium-responsive members from selenium hyperaccumulator Cardamine hupingshanensis - Jingyu Xie; Yushan Chen; Jingyi Liu; Xinying Gao; Xinyi Liang; Anjun Chen; Zhixin Xiang; Shengcai Chen; Zhi Hou; Yanke Lu; Qiaoyu Tang; Yifeng Zhou (Plant Science, 2026)

Defect and multi-interface synergistic engineering of a sulfide heterostructure with spatially separated redox sites enabling efficient and stable photocatalytic H2 evolution - Yachong Wang; Chaoyue Zheng; Youlin Wu; Qingyang Pang; Yanke Yang; Jihuai Wu; Meihua Xin; Cheng Peng; Jiamin Lu; Yiming Xie (Chemical Engineering Journal, 2026)

A highly efficient nanocopper hydroxide activates plant immune resistance and confers tolerance to salt and drought stress in rice - Chongchong Lu; Zimeng Li; Taizhong Huang; Muhammad Zunair Latif; Haifeng Liu; Mingxia Hao; Yanke Jiang; Yingzhe Yue; Jian Zhang; Miaomiao Deng; Qian Du; Sifan Yang; et al. (Chemical Engineering Journal, 2026)

Vacancy defect regulation of the spatial local electronic states and energy band structure of CoNi₂S₄/VsCdS Schottky junction for improved photocatalytic hydrogen evolution - Qingyang Pang; Youlin Wu; Yanke Yang; Jihuai Wu; Jiamin Lu; Yiming Xie (Chemical Engineering Journal, 2025)

Sulfotransferases in Cardamine hupingshanensis: Identification, expression, and regulatory role in selenium metabolism under selenium stress - Jing Xiao; Qian Yuan; Anjun Chen; Xixi Zeng; Yanke Lu; Zhixin Xiang; Zhi Hou; Qiaoyu Tang; Yifeng Zhou (Plant Science, 2025)

SlXTH1, a xyloglucan endotransglucosylase/hydrolase in halophyte Suaeda liaotungensis, negatively regulates Arabidopsis seed germination under salt stress - Jieqiong Song; Haoran Ding; Nuo Cheng; Xinxin Li; Yanke Lu; Hongfei Wang; Changping Li; Qiuli Li (Plant Science, 2025)

Synergistic construction of efficient heterojunction structures through vacancy engineering and nanoscale effects to enhance photodegradation efficiency - Qingyang Pang; Chaoyue Zheng; Youlin Wu; Xuan Wang; Yachong Wang; Yanke Yang; Teng Li; Canzhong Lu; Yiming Xie; Fuda Yu (Journal of Water Process Engineering, 2025)

Chitosan-glutaraldehyde graphene oxide aerogel for extraction of polybrominated and -chlorinated carbazoles in lotus root - Yanke Lu; Pengfei Li; Liuliu Cheng; Lianfeng Ai; Jiankun Cao; Hongyuan Yan (Food Chemistry, 2025)

Molecularly imprinted resin modified with ionic liquid for dispersive filter extraction and determination of perfluoroalkyl acids in eggs - Yanke Lu; Hongyuan Yan; Pengfei Li; Yehong Han; Shigang Shen (Food Chemistry, 2024)

Transfer and risk assessment of fipronil in laying hen tissues and eggs - Zhiwei Wang; Ziyan Du; Yanke Shi; Peipei Qi; Shanshan Di; Huiyu Zhao; Xiaofeng Ji; Chunbo Lu; Xinquan Wang (Science of The Total Environment, 2024)

Gene identification, expression analysis, and molecular docking of SAT and OASTL in the metabolic pathway of selenium in Cardamine hupingshanensis - Yushan Chen; Yao Li; Guoqiang Luo; Cihang Luo; Zhijing Xiao; Yanke Lu; Zhixin Xiang; Zhi Hou; Qiang Xiao; Yifeng Zhou; Qiaoyu Tang (Plant Cell Reports, 2024)
Key message Identification of selenium stress-responsive expression and molecular docking of serine acetyltransferase (SAT) and O -acetyl serine (thiol) lyase (OASTL) in Cardamine hupingshanensis. Abstract A complex coupled with serine acetyltransferase (SAT) and O -acetyl serine (thiol) lyase (OASTL) is the key enzyme that catalyzes selenocysteine (Sec) synthesis in plants. The functions of SAT and OASTL genes were identified in some plants, but it is still unclear whether SAT and OASTL are involved in the selenium metabolic pathway in Cardamine hupingshanensis . In this study, genome-wide identification and comparative analysis of ChSAT s and ChOASTL s were performed. The eight ChSAT genes were divided into three branches, and the thirteen ChOASTL genes were divided into four branches by phylogenetic analysis and sequence alignment, indicating the evolutionary conservation of the gene structure and its association with other plant species. qRT-PCR analysis showed that the ChSAT and ChOASTL genes were differentially expressed in different tissues under various selenium levels, suggesting their important roles in Sec synthesis. The ChSAT1;2 and ChOASTLA1;2 were silenced by the VIGS system to investigate their involvement in selenium metabolites in C. hupingshanensis . The findings contribute to understanding the gene functions of ChSAT s and ChOASTL s in the selenium stress and provide a reference for further exploration of the selenium metabolic pathway in plants.

Long-term straw return enhanced crop yield by improving ecosystem multifunctionality and soil quality under triple rotation system: An evidence from a 15 years study - Runxia Huo; Jinlong Wang; Kunkun Wang; Yanke Zhang; Tao Ren; Xiaokun Li; Rihuan Cong; Jianwei Lu (Field Crops Research, 2024)

Ant nest-like hierarchical porous imprinted resin-dispersive solid-phase extraction for selective extraction and determination of polychlorinated biphenyls in milk - Yanke Lu; Qi Shen; Chengcheng Zhai; Hongyuan Yan; Shigang Shen (Food Chemistry, 2023)

Novel molecularly imprinted phenolic resin–dispersive filter extraction for rapid determination of perfluorooctanoic acid and perfluorooctane sulfonate in milk - Jing Ren; Yanke Lu; Yehong Han; Fengxia Qiao; Hongyuan Yan (Food Chemistry, 2023)

Involvement of MEM1 in DNA demethylation in Arabidopsis - Yanke Lu; Jie Dai; Liu Yang; Yumei La; Shaoxia Zhou; Sheng Qiang; Qianqian Wang; Feng Tan; Yufeng Wu; Weiwen Kong; Honggui La (Plant Molecular Biology, 2020)

Paecilomyces variotii extracts (ZNC) enhance plant immunity and promote plant growth - Chongchong Lu; Haifeng Liu; Depeng Jiang; Lulu Wang; Yanke Jiang; Shuya Tang; Xuwen Hou; Xinyi Han; Zhiguang Liu; Min Zhang; Zhaohui Chu; Xinhua Ding (Plant and Soil, 2019)

Analysis of the DNA methylation patterns and transcriptional regulation of the NB-LRR-encoding gene family in Arabidopsis thaliana - Weiwen Kong; Bin Li; Qianqian Wang; Bin Wang; Xiaoke Duan; Li Ding; Yanke Lu; Li-Wei Liu; Honggui La (Plant Molecular Biology, 2018)

Scoring the collective effects of SNPs: association of minor alleles with complex traits in model organisms - DeJian Yuan; ZuoBin Zhu; XiaoHua Tan; Jie Liang; Chen Zeng; JieGen Zhang; Jun Chen; Long Ma; Ayca Dogan; Gudrun Brockmann; Oliver Goldmann; Eva Medina; et al. (Science China Life Sciences, 2014)